Gelation properties and glucose-sensitive behavior of phenylboronic acid based low-molecular-weight organogels. Issue 14 (8th April 2015) - Xu, Long; Hu, Yalong; Liu, Miaochang; Chen, Jiuxi; Huang, Xiaobo; Gao, Wenxia; Wu, Huayue
Abstract: A series of phenylboronic acid (PBA)-based low-molecular-weight gelators with different hydrocarbon chain lengths (C2–C11) were designed and synthesized. These gelators gelated five solvents efficiently at relatively low concentration with interesting aggregates of nanofibers, thin films, spherical thin shells, and microspheres piled with nanofibers. The gelation ability increased with the chain length increasing up to C11, which has the lowest critical gelation concentration (CGC) of 0.19 wt %. FTIR and 1 H NMR measurements suggested that van der Waals of alkyl chains, H-bonding, and π–π stacking interactions had an important contribution in gelation process and self-assembly. For all the gelators, their glucose-response increased along with the increasing concentration of glucose solution. However, the recognition and responsive rate to glucose were weakened gradually with the alkyl chain length increasing for the gelators. Therefore, glucose-sensitivity of these PBA-based organogels could be modulated through alkyl chain length. Graphical abstract: